Pengaruh Lingkungan Kerja, Kompetensi dan Motivasi Kerja terhadap Kinerja Karyawan: Studi Kasus Pada Karyawan PT Citra Media Nusa Purnama, Jakarta Barat - Evita Dwi Wardhani; Widi Wahyudi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of Work Environment (X1), Competence (X2), and Work Motivation (X3) on Employee Performance (Y). The research was conducted at PT Citra Media Nusa Purnama with a sample of 96 employees located in West Jakarta. Data were collected using questionnaires and analyzed through multiple linear regression with the help of SPSS version 30 at a 5% significance level. The results indicate that Competence (X2) and Work Motivation (X3) have a positive and significant effect on Employee Performance (Y), while Work Environment (X1) does not show a significant effect. However, when tested simultaneously, the three variables together influence employee performance. These findings highlight that competence is a crucial factor in improving performance, particularly through training programs, mastery of technical knowledge, and the development of operational skills. In addition, motivation plays an essential role and can be strengthened by providing challenging tasks, recognizing employee achievements, encouraging initiative, and granting autonomy in decision-making. Although the work environment did not show a significant partial effect, it remains important to create a comfortable and supportive atmosphere to ensure employee well-being and productivity. Overall, this research emphasizes the importance of competence development and motivation strategies as managerial priorities to enhance employee performance in the organization.